Novel serum biomarkers for early diagnosis of gestational diabetes mellitus—a review - Michał Kunicki; Natalia Rzewuska; Paulina Sopońska; Agata Pawłosek; Iwona Sowińska; Anna Kloska (Gynecological Endocrinology)
Gestational diabetes mellitus (GDM) affects 9–25% of pregnancies. Undiagnosed or poorly managed GDM is associated with both short- and long-term complications in the fetus and mother. The pathogenesis of GDM is complex and has not yet been fully elucidated. Several biomarkers found in maternal serum have the potential for the early diagnosis of GDM. The aim of this narrative review was to explore novel biomarkers that have not been comprehensively described in previous reviews. We believe these biomarkers may allow for the detection of GDM in the early stages of pregnancy, enabling timely proper treatment and potentially preventing complications for both the mother and the fetus.